GAGASAN MENCEGAH TIMBULNYA CALON TUNGGAL PADA PEMILIHAN KEPALA DAERAH SERENTAK DALAM PERSPEKTIF DEMOKRASI DI INDONESIA - Siti Nurrahmah; Emilda Firdaus; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The issuance of the 100 / PUU-XIII / 2015 Constitutional CourtDecision giving birth to Law Number 10 of 2016 concerning the Establishment ofGovernment Regulations in lieu of Law Number 1 of 2014 concerning Election ofGovernors, Regents and Mayors to Act -Well. In Article 54C paragraph (1,2 and3) it is stated that regional head elections with a single candidate may be carriedout with stipulated provisions. According to the author's assumptions, the articleopens the opportunity for a single candidate to increase. In fact, the constitutionin Article 18 paragraph (4) of the 1945 Constitution has mandated democraticregional elections. Thus, the election of regional heads with a single candidatecan lead to the degradation of democratic values adopted by Indonesia. So, in thisstudy produce two main and very important things that can be concluded. First,the implications of the emergence of a single candidate in the regional headelections simultaneously in the perspective of democracy in Indonesia. Second,the idea of preventing the emergence of a single candidate in regional headelections simultaneously in a democratic perspective.This type of research is normative legal research, because in this study,the authors conducted a literature study, In addition, the author also conductedresearch on the principles and rules of law contained in the law thataccommodate this research. This is done to explain the legal theories relating toregional head elections and carried out with a single candidate, especially in theIndonesian state that adheres to the principle of democracyAuthor's suggestion; First, for legislators to revise the law onsimultaneous regional head elections and related regulations so as not to create asingle candidate, especially reducing the percentage threshold that must be metby political parties. Second, it requires political parties to carry out politicalregeneration for members of political parties in an effort to prepare a generationof qualified leaders. Political parties must carry out political education onsociety, and political socialization so that the public knows who the candidateswill be from the political party.Keywords: Single Candidates, Regional Head Elections, Democracy.